Physical activity status among health science students of Chitwan, Nepal - Adhikari, Kishor; Neupane, Sadikshya; Sapkota, Sachin; Khanal, Gayatri (Journal of Chitwan Medical College, 2021)
Background: Physical inactivity has become a major public health concern in todays’ world. Evidences suggest that nearly one-fifth of the overall risk for coronary heart disease, type 2 diabetes, breast cancer, colon cancer is due to physical inactivity. The aim of present study is to assess the physical activity status among health science students in Chitwan District of Nepal. Methods: Present study is a cross-sectional study conducted among health science students of Chitwan District identified through non-probability sampling technique. Ethical approval was obtained from CMC IRC. Information on physical activity was gathered using the self-reported Global GPAQ – 16 items. A final activity response from each student was summed into MET/minutes per week, which was further classified as: inactive, low active, moderately active and highly active in terms of total MET minute/week. Descriptive and inferential analysis was done through this IBM SPSS software version 20. Results: More than two-third of students reported their status as low active. Nearly 7% were physically inactive. About 93% of the health science students met the minimum WHO recommendation for physical activity (≥600 MET-minutes/week). The difference on physical activity status according to gender and age groups was found statistically significant (p<0.005). Conclusions: There was huge proportion of students with low level of physical activity. There is need for focusing on health information system to aware public regarding the importance of physical activity.